2023
DOI: 10.3389/fcvm.2022.1105413
|View full text |Cite
|
Sign up to set email alerts
|

Predictive effect of different blood lipid parameters combined with carotid intima-media thickness on coronary artery disease

Abstract: BackgroundBlood lipids disorder and atherosclerosis are closely related to coronary artery disease (CAD). This study aims to compare different blood lipid parameters combined with carotid intima-media thickness (cIMT) in predicting CAD.MethodsThis was a retrospective study including patients who underwent coronary angiography for highly suspected CAD. Blood samples were taken for lipid profile analysis and cIMT was evaluated by carotid ultrasound. Logistic analysis was used to establish different models of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…A recent retrospective study that enrolled 1395 patients, found better capability of an existing model for predicting coronary artery disease after adding Lp(a) compared to other lipid parameters. The new model which incorporated Lp(a) achieved an NRI of 12.8% and significant improvement in accuracy, measured by IDI [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study that enrolled 1395 patients, found better capability of an existing model for predicting coronary artery disease after adding Lp(a) compared to other lipid parameters. The new model which incorporated Lp(a) achieved an NRI of 12.8% and significant improvement in accuracy, measured by IDI [ 32 ].…”
Section: Discussionmentioning
confidence: 99%